Risk Management of High-Rise Buildings in Coastal Areas: A Bibliometric Review Using Vosviewer - Rahmat Hermawan; Andri Irfan Rifai; Mulia Pamadi; Susanty Handayani (PT. Publikasiku Academic Solution, 2024)
The research aims to provide a comprehensive and quantitative analysis of the existing literature on risk management of high-rise buildings in coastal areas, identify research trends, and evaluate the impact of scientific publications in this field. This research focuses on the importance of risk management in high-rise buildings located in coastal areas, considering the increasing sea levels, extreme weather events, and high population density. This research uses bibliometric analysis, specifically VOSviewer software, to analyze data from 1000 publications with keywords such as Risk Management, Coastal Area, High-rise building, and Environmental Risk from 2000 to 2023. The research involves extensive bibliometric data analysis, including keyword frequency analysis, time trends, and relationships between authors and journals. The research results are expected to provide valuable insights for researchers and practitioners in developing practical and sustainable risk management strategies for high-rise buildings in coastal areas. The conclusion of this study is that the research trend on risk management of high-rise buildings in coastal areas is still an interesting topic around the world and will continue to develop continuously.